KEBIJAKAN PEMERINTAH DALAM PENYELESAIAN SENGKETA DAN KONFLIK PERTANAHAN: Government Policy In Resolving Land Disputes And Conflicts - Kartiwi, Mulia (Fakultas Hukum Universitas Komputer Indonesia, 2024)
The Consortium for Agrarian Reform reported that agrarian conflicts increased in 2022. The area of land in conflict is up tp 1.04 million hectares (ha), which affected 346,402 households in 459 regions in Indonesia. Based on this condition, it is necessary to conduct research which aims to determine the factors that cause land disputes and to identify government policies to resolve the land conflicts. This research is descriptive analytical study with a normative juridical approach in form of literature study on secondary data containing legal norms, then analyzed qualitatively. In result shows that the factors causing land conflicts are the limited availability of land which results in land ownership inequality Implementation of land registration is still experiencing obstacles; Law enforcers are not all committed to implementing laws and regulations consequently and consistently. To resolve land conflicts, the government implemented a policy in the form of Minister of Agrarian Affairs and Spatial Planning/National Land Agency Number 6 of 2018 concerning Number 6 of 2018 concerning Complete Systematic Land Registration in conjunction with Presidential Instruction Number 2 of 2018 concerning the Acceleration of Complete Systematic Land Registration in All Regions of the Republic of Indonesia, to ensure certainty and protection to landowners. Through those policy, the implementation of land registration is accelerated and carried out simultaneously by the government at no cost. Furthermore, the Minister of Agrarian Affairs and Spatial Planning/National Land Agency Number 21 of 2020 concerning Handling and Settlement of Land Cases, one of which is through mediation, inspite of its weakness.